Compound muscle action potential duration ratio for differentiation between Charcot-Marie-Tooth disease and CIDP. (February 2023) - Kitaoji, Takamasa; Noto, Yu-ichi; Kojima, Yuta; Tsuji, Yukiko; Kitani-Morii, Fukiko; Mizuno, Toshiki; Nakagawa, Masanori
Highlights: The CMAP duration ratio is an electrophysiological index reflecting the distribution of demyelination. The CMAP duration ratio can effectively distinguish demyelinating CMT and CIDP. The CMAP duration ratio may be of diagnostic utility in a clinical setting. Abstract: Objective: To elucidate the utility of the proximal to distal compound muscle action potential (CMAP) duration ratio to distinguish between demyelinating Charcot-Marie-Tooth disease (CMT) and chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) compared with nerve ultrasound. Methods: Thirty-nine demyelinating CMT patients and 19 CIDP patients underwent nerve conduction studies (NCS) and nerve ultrasound. NCS parameters including CMAP duration ratio calculated by dividing the value at the proximal site by that at the distal site and nerve cross-sectional area (CSA) measured by ultrasound were compared between the two groups. The diagnostic sensitivity and specificity of each parameter were analysed. Results: CMT patients showed a significantly lower CMAP duration ratio than CIDP patients (p < 0.05). The area under the curve (AUC) value of the CMAP duration ratio exceeded 0.95 when CMT was considered "positive", and a cut-off value of 1.13 resulted in high diagnostic sensitivity and specificity (84.6 and 100 % for median nerve, 97.4 and 85.7 % for ulnar nerve, respectively), whereas the AUC value of nerve CSA ranged from 0.70 to 0.81. Conclusions: The CMAP duration ratio could effectively distinguish between demyelinating CMT and CIDP. Significance: Adding the CMAP duration ratio to a routine NCS may improve the accuracy of the diagnosis of demyelinating CMT.